Identification of Critical Success Factors in Information Systems Implementation Projects - M. A. Orlov (North-West institute of management of the Russian Presidential Academy of National Economy and Public Administration, 2020)
Currently, government and commercial organizations are increasingly dependent on the use of various information systems. Investments in information systems fi their place in enterprises of various sizes, from small to large. The main goal, which forces enterprises to imple ment information systems, is the need to obtain centralized access to information and facilitate the procedure for its receipt, storage and processing in order to increase productivity and increase the efficiency of production activities. Currently, information systems are a tool for standardizing business processes and offer a variety of functionalities based on best practices. At the same time, the implementation of the system is a difficult task (there is a very high percentage of unsuccessful projects), requiring great efforts, careful reflection and good planning, as well as a detailed analysis of the factors that are critical for the successful implementation of the system. Right now, the urgent need for finding new tools and opportunities to increase the number of successful projects. The article is devoted to critical factors affecting projects for the implementation of information systems in enterprises. The scientific works of domestic and foreign scientists and practitioners are analyzed and reviewed in order to identify factors that are called critical success factors that directly affect such projects in order to determine which critical factors were empirically recognized as “critical”. To evaluate each factor and the relationship between them, the author uses statistical analysis. The study also uses both quantitative and qualitative analysis of data obtained from scientific papers. The data collected were analyzed and 10 key success factors identified. Critical success factors are an effective and important tool for achieving the goals of projects for the implementation of information systems in enterprises, which will contribute to the correct decision-making and improve the effectiveness of projects and, as a result, the achievement of strategic goals that bring long-term benefits to the enterprise.